2022
DOI: 10.1590/1678-4685-gmb-2021-0307
|View full text |Cite
|
Sign up to set email alerts
|

In the screening of alternative insecticides to control Aedes aegytpti larvae 2-methylanthraquinone showed no genotoxicity and low toxicity to zebrafish (Danio rerio)

Abstract: The threats posed by insecticide resistance to Aedes aegypti in the context of controlling dengue have led to an urgent search for an environmentally safer alternative chemical with more effective larvicidal properties. Among many molecules tested, 2-methylanthraquinone showed the lowest LC50 for A. aegypti in a previous study and the highest LC50 for zebrafish embryos. Embryos were exposed at concentrations of 1.0, 2. 19, 4.78, 10.46, 22.87, 50.0 and 100.0 mg/L, and malformations and mortality were significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…The comet assay is a more sensitive endpoint than the micronucleus test. Considering the biochemical markers used, it is known that the assessment of AChE levels has been used as an indicator of in vivo neurotoxicity and the GST is involved with detoxification xenobiotics [ 50 ]. In the present study, MPs caused alterations in some biochemical biomarkers, such as AChE inhibition in the zebrafish head and GST increased activity in the gills.…”
Section: Discussionmentioning
confidence: 99%
“…The comet assay is a more sensitive endpoint than the micronucleus test. Considering the biochemical markers used, it is known that the assessment of AChE levels has been used as an indicator of in vivo neurotoxicity and the GST is involved with detoxification xenobiotics [ 50 ]. In the present study, MPs caused alterations in some biochemical biomarkers, such as AChE inhibition in the zebrafish head and GST increased activity in the gills.…”
Section: Discussionmentioning
confidence: 99%
“…GST has as main function the biotransformation and elimination of xenobiotics and defense of cells against oxidative stress, and LDH is an enzyme found in most tissues that plays an important role in glucose metabolism within the body. 40 After 96 h of exposure to 3a, it was observed that the organisms exposed to the last concentration (0.25 µg mL -1 , *P < 0.05) showed significant decreases in the activities of these enzymes (Figure 4). These effects may be correlated with the sublethal and lethal effects seen in the embryotoxicity test.…”
Section: -Biochemical Testsmentioning
confidence: 92%